Screening of Legionella pneumophila from Well Water in Magetan Regency, Indonesia - Hapsari, Nafisah Nurul; Kurniawan, Muhammad Ridho Hafid; Sucipto, Teguh Hari; Fajar, Nur Syamsiatul; Herupradopo, Eduardus Bimo Aksono; Fauziyah, Shifa; Widya, Alicia Margaretta; Aquaresta, Febriana; Sin War Naw (Indonesian Journal of Tropical and Infectious Disease, 2023)
Legionellosis is a respiratory infection caused by Legionella pneumophila, a bacterium that can infect protozoa and human lung cells. The disease can be mild or severe, and sometimes fatal, especially in immunocompromised people. Some types of antibiotics that can be used to treat Legionella disease are macrolides such as rifampicin, azithromycin and clarithromycin, as well as fluoroquinolones such as levofloxacin and moxifloxacin. The aim was to investigate the distribution and prevalence of Legionella in well water. This study collected and tested water samples from a different well water in Magetan Regency, East Java, Indonesia using DNA extraction, two-step PCR methods, and visualization with 1.5% agarose gel in UV transluminator. The results were visualized with QGIS 3.28.6 and compared with other tests. The results showed that none of the eight water samples were contaminated with L. pneumophila compared with positive control (403 bp).